2018
DOI: 10.2147/opth.s162019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal ranibizumab on serous retinal detachment in branch retinal vein occlusion

Abstract: PurposeThe aim of this study was to evaluate the effect of initial intravitreal ranibizumab injection on visual acuity (VA) and central macular thickness (CMT) for the treatment of macular edema (ME) with and without serous retinal detachment (SRD) secondary to branch retinal vein occlusion (BRVO).Materials and methodsFifty-two BRVO eyes, treated with intravitreal ranibizumab injection for ME with and without SRD, were retrospectively reviewed. Patients were divided into two groups according to spectral domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Several studies from literature have shown significant improvement in RVO patients with SRD both functionally and morphologically. Dogen et al studied changes of central macular thickness and VA in BRVO patients with and without SRD after intravitreal ranibizumab injection and found SRD group showed greater improvement of macular morphology [13]. Pinazo et al evaluated response to ranibizumab of BRVO patients with and without SRD and found an improvement of + 15 letters of BCVA and − 205.9 μm of central foveal thickness in patients with SRD over a mean follow-up of 12.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from literature have shown significant improvement in RVO patients with SRD both functionally and morphologically. Dogen et al studied changes of central macular thickness and VA in BRVO patients with and without SRD after intravitreal ranibizumab injection and found SRD group showed greater improvement of macular morphology [13]. Pinazo et al evaluated response to ranibizumab of BRVO patients with and without SRD and found an improvement of + 15 letters of BCVA and − 205.9 μm of central foveal thickness in patients with SRD over a mean follow-up of 12.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a more marked improvement of macular structure was achieved in patients with SRD than in those without SRD. These ndings may be explained by the strong association of in ammatory factors and extensive morphological changes with the occurrence and/or recurrence of SRD, thus patients with SRD have better improvement of macular structure by anti-VEGF treatment [13]. Based on previous reports and the current study, we suggest that if SRD is observed only at the rst presentation, it does not necessarily predict poor visual prognosis because anti-VEGF treatment can alleviate damage to foveal photoreceptors in the outer segment by restoring the ELM barrier and improving macular structure and function [15].…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptor damage is more likely to occur with prolonged and/or repeated severe retinal edema. From short-term studies, patients who had SRD at initial presentation tended to have worse visual acuity during the follow-up [13]. Broken retinal capillaries lead to sub-retinal uid, thickening the retina.…”
Section: Discussionmentioning
confidence: 99%
“…По нашим предположениям, данный факт может быть связан не только с истинной толщиной, но и с часто встречающейся ОНЭ, которая автоматически увеличивает высоту макулярного отека. На исходно бóльшую толщину сетчатки в фовеа у пациентов с наличием ОНЭ указывали и другие авторы [24][25][26].…”
Section: обсуждение результатовunclassified